IMPLEMENTATION OF PROJECT BASED LEARNING MODEL A SMK NEGERI 1 ABUNG SELATAN TO IMPROVE COLLABORATE SKILL - Anggita Dara Nacita; Ratih Handayani (Hipotenusa Journal of Research Mathematics Education (HJRME), 2026)
The objective of this study is to examine the effect of implementing the Project Based Learning (PjBL) model on the collaboration skills of Grade X students at SMK Negeri 1 Abung Selatan. The method employed was a quasi-experimental design with a pretestposttest structure involving both an experimental class and a control class. Collaboration skill data were collected through questionnaires and authentic assessments. The analysis process included normality tests, homogeneity tests, t-tests, and N-Gain calculations. The findings revealed that although the N-Gain scores from the questionnaires in the experimental class showed greater achievement compared to the control class, the authentic assessment results were actually higher in the control class. The t-test indicated no significant difference between the two groups, suggesting that the application of PjBL did not lead to a meaningful improvement in collaboration skills. This condition was influenced by limited project time, suboptimal role distribution, and students adaptation process to the new learning method. More structured project planning is recommended for future research